2016
DOI: 10.1002/mrd.22640
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mRNA populations of short and long bovine conceptuses on Day 15 of gestation

Abstract: The majority of pregnancy loss in cattle occurs between Days 8 and 16 of gestation, coincident with the initiation of conceptus elongation and the onset of maternal recognition of pregnancy. Differences in conceptus length on the same day of gestation may be related to an inherent lack of developmental competency or may simply be a consequence of asynchrony with the maternal environment. The objective of this work was to characterize differential patterns of mRNA expression between short and long bovine concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 101 publications
9
61
0
Order By: Relevance
“…These data support the hypothesis that conceptus regulation of gene expression in the endometrium is complex and involves factors other than IFNT that may have a biological role in pregnancy establishment. The findings are consistent with the presence of unique proteins in ULF of pregnant heifers on Day 16 and produced by short-term in vitro cultured Day 16 conceptuses (Forde et al, 2015) and those of Bartol et al (1985) who demonstrated that the fully elongated bovine conceptus produces a significant number of proteins when cultured in vitro. Further, Spencer et al (2013) demonstrated that the bovine conceptus produces prostaglandins, which can modify the endometrium prior to pregnancy recognition.…”
Section: Response Of the Endometrium To In Vivo Or In Vitro Derived Csupporting
confidence: 85%
See 1 more Smart Citation
“…These data support the hypothesis that conceptus regulation of gene expression in the endometrium is complex and involves factors other than IFNT that may have a biological role in pregnancy establishment. The findings are consistent with the presence of unique proteins in ULF of pregnant heifers on Day 16 and produced by short-term in vitro cultured Day 16 conceptuses (Forde et al, 2015) and those of Bartol et al (1985) who demonstrated that the fully elongated bovine conceptus produces a significant number of proteins when cultured in vitro. Further, Spencer et al (2013) demonstrated that the bovine conceptus produces prostaglandins, which can modify the endometrium prior to pregnancy recognition.…”
Section: Response Of the Endometrium To In Vivo Or In Vitro Derived Csupporting
confidence: 85%
“…The role of P4 in uterine receptivity is unequivocal Spencer et al, 2016). Low circulating P4 concentrations in the first week after ovulation, as frequently occurs in highproducing lactating dairy cows, are associated with under-developed conceptuses with an altered transcriptomic signature (Barnwell et al, 2016) and a low likelihood of establishing pregnancy (Wiltbank et al, 2016). On the other hand, elevated concentrations of circulating P4 in the period immediately after conception have been associated with advanced conceptus elongation (Carter et al, 2008), increased IFNT production (Mann and Lamming 2001), and greater pregnancy rates in cattle and sheep (Ashworth et al, 1989;Stronge et al, 2005;McNeill et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in conceptus length on the same day of gestation may be related to an inherent lack of developmental competence or may simply be a consequence of asynchrony with the maternal environment (Pope 1988). Barnwell and coworkers characterised differential patterns of mRNA expression between short (mean length of 4.2 ± 0.1 mm) and long (24.7 ± 1.9 mm) bovine conceptuses recovered on Day 15 of gestation (Barnwell et al 2016). A total of 348 genes were differentially expressed (221 genes upregulated and 127 downregulated in long compared to short conceptuses) suggesting inherent differences exist between such conceptuses and not just differences in the conceptuses's ability to produce IFNT.…”
Section: Variation In Conceptus Sizementioning
confidence: 99%
“…Analysis identified differentially regulated genes organized in nine gene clusters forming a sequential transcript dynamics across these developmental stages. These data have been expanded upon by more recent studies (Valour et al, 2014;Barnwell et al, 2015Barnwell et al, , 2016Ribeiro et al, 2016a, b). Flechon et al (1986) cut day 12 ovine blastocysts into pieces and cultured them in vitro for 24 h, to produce structures called trophoblastic vesicles (TV, blastocysts without the embryonic disc).…”
Section: Progesterone and Conceptus Elongationmentioning
confidence: 84%
“…In this regard, Barnwell et al (2016) recently characterized differential patterns of mRNA expression between short and long bovine conceptuses recovered on day 15 of gestation which may be indicative of conceptus survival.…”
Section: Final Remarksmentioning
confidence: 99%